CENSORSHIP DURING THE GOVERNMENTS OF VELASCO ALVARADO AND FUJIMORI - Espinoza Bonifaz, Augusto R. (2023)
The objective of the research was to compare the governments of Juan Velasco Alvarado and Alberto Fujimori Fujimori in Peru, focusing on the censorship of the press and its impact on society. In addition, the most relevant newspaper front pages will be observed, at our discretion, in order to make a comparative analysis of the degree of censorship of the news media. Regarding the design of the research, it was of a qualitative approach, theoretical and documentary type, the inductive, analytical and historical method was used, and at an explanatory level. In the case of Juan Velasco Alvarado, who came to power through a coup, he implemented social reforms and had gradual control of the media. This implied regulating the criticism of the press to favor his government and avoid the dissemination of information contrary to the revolution. On the other hand, Fujimori, with broad popular support, clung to power under the excuse of fighting terrorism. He used economic resources and manipulation of the media to influence public opinion in favor of his government and against his opponents. Additionally, different positions of authors regarding media censorship were analyzed, both against and in favor of freedom of expression. In turn, we will talk about two theories that complement political censorship. Finally, it was concluded that both regimes manipulated the media, covering up their negative actions and seeking to remain in power, although under different instruments